Independent risk factors and outcomes for ventilator-associated pneumonia due to multidrug-resistant organisms after cardiac valvular surgery - XiaoLiang Chen; LaiYha Yan; ShunYing Zhao; XiaoYan Hu; GuoFeng Shao; Ni Li; LinWen Zhu (Frontiers in Cardiovascular Medicine)
BackgroundAlthough numerous studies have documented the risk factors for ventilator-associated pneumonia (VAP) after cardiac surgery, most of these studies included heterogeneous patient populations. This study aimed to explore the risk factors for VAP caused by multidrug-resistant organisms (MDRO) in patients admitted to the cardiosurgery intensive care unit (CSICU) following cardiac valvular surgery.MethodsThis was a single-center, retrospective study. The clinical data of adult VAP patients following cardiac valvular surgery from January 2021 to December 2023 were analyzed. Patients were divided into MDRO VAP and non-MDRO VAP groups. Perioperative clinical data and postoperative follow-up results were collected for both groups. Univariable and multivariable logistic regression analyses were performed to identify risk factors for MDRO VAP, and the outcomes of MDRO VAP patients were analyzed. The species of pathogens isolated from the VAP patients were also investigated.ResultsA total of 109 VAP patients were included in this study, including 47 patients with MDRO VAP and 62 patients with non-MDRO VAP. Multivariable logistic regression analysis identified that independent risk factors for MDRO VAP included preoperative hypoalbuminemia (OR, 0.838; CI, 0.733–0.957; p = 0.009), prolonged mechanical ventilation (OR, 1.173; CI, 1.005–1.369; p = 0.043), and extended broad-spectrum antibiotic therapy (OR, 1.112; CI, 1.019–1.213; p = 0.018). Patients with MDRO VAP had significantly longer ICU stays, total hospital stays, and higher hospitalization costs than non-MDRO VAP patients. The in-hospital mortality rate of the MDRO VAP group was significantly higher than that of the non-MDRO VAP group (29.79% vs. 1.61%, p < 0.001). Gram-negative bacilli were the predominant pathogens in MDRO VAP patients (97.87%), with the highest rate of Pseudomonas aeruginosa (29.79%).ConclusionPostoperative MDRO VAP in patients undergoing cardiac valvular surgery is linked to severe clinical outcomes. Greater attention should be given to patients with prolonged mechanical ventilation, extended broad-spectrum antibiotic therapy, and preoperative hypoalbuminemia to prevent MDRO VAP infections.